ACTORS CAUSING TEENAGERS TO JOIN MOTORCYCLE COMMUNITIES IN THE PARAK LAWEH PULAU AIA NAN XX VILLAGE LUBUK BEGALUNG DISTRICT PADANG CITY - Henmia, Zalmi; Rahmadani, Sri; Yatim, Yenita (Jurnal Mamangan, 2025)
Village, Pulau Aia Nan XX, Lubuk Begalung District. The presence of motorcycle gangs here attracts many adolescents, particularly the RGA (Horrible House) community, which is popular among young people. Therefore, this study aims to analyze the factors that contribute to adolescents joining motorcycle gangs in Parak Laweh Village, Pulau Aia Nan XX, Lubuk Begalung District, Padang City. This research uses a qualitative descriptive method. The theory used in this study is the Social Ecology Theory developed by Urie Bronfenbrenner. Informants were selected using a purposive sampling technique involving adolescent motorcycle gang members, peers, parents, and the local community. Data were collected through non-participant observation, in-depth interviews, and documentation studies. The data were then analyzed using the Milles and Huberman interactive data analysis model. The results of the study show that there are four factors that cause teenagers to join motorcycle gang communities in Parak Laweh Village, Pulau Aia Nan XX, namely: (1) Factors of Weakening Family Affection Function, (2) Factors of Peer Influence, (3) Factors of Permissive Social Environment, (4) Factors of Popular Culture Influence. Therefore, based on the analysis with Social Ecology Theory, this shows that the involvement of teenagers in motorcycle gang communities is the result of complex interactions between individuals and various microsystem, mesosystem, exosystem, macrosystem, and chronosystem environmental systems that are interrelated in shaping adolescent behavior.